Morphology and DNA barcoding reveal a new species of eagle ray from the Southwestern Atlantic: Myliobatis ridens sp. nov. (Chondrichthyes, Myliobatiformes, Myliobatidae) - Ruocco, Natalia Lorena (2012)
Two species of Myliobatis, the southern eagle ray M. goodei Garman and the bullnose eagle ray M. freminvillii Le Sueur, have long been recognized to occur in coastal Argentinean waters. Several unusual specimens belonging to the family Myliobatidae, have been recently collected from off the Buenos Aires Province, Argentina. These specimens clearly belong to the genus Myliobatis, since they have a broad disk with long sharply pointed pectoral fins, a projecting snout, tail very long and thin, and smaller dorsal fin set farther back on the tail, well beyond the pelvic fins. However, the specimens were distinct from all their sympatric congeners in several characters, and they are described here as a new species. Myliobatis ridens sp. nov. is distinguished from M. goodei in having a relatively shorter snout, a wider interorbital space, a wider mouth, and a different shape in the ventral and dorsal marginal cartilages of the claspers than the latter; and from M. freminvillii by having smaller eyes, a smaller dorsal fin, a plain dorsal coloration, and a different shape of the dorsal marginal cartilage of the claspers. In order to test this morphological differentiation, cytochrome c oxidase I (COI) sequence data were obtained from the new species and compared with those of its congeners. Analysis of COI sequences showed a congeneric sequence divergence higher than 6%, supporting the species differentiation. Therefore combining both, traditional taxonomy and DNA barcoding, a new eagle ray species, Myliobatis ridens sp. nov., from the Southwest Atlantic Ocean was discovered.